Primary bone diffuse B cell lymphoma of the thoracic spine: a rare entity - Akçay, Emrah; Benek, Hüseyin Berk; Yılmaz, Hakan; Tabanlı, Alper; Yurt, Alaattin (The European Research Journal, 2023)
Primary bone lymphoma is a rare entity, accounting for approximately 3-7% of malignant bone tumors, 5% of extra-nodal lymphomas and